Contaminación por coliformes fecales debido al vertimiento de aguas residuales en la playa El Murciélago, Manta-Manabí - Loor Barrezueta, Yulio Santiago (2023)
The amount of fecal coliforms in seawater from beaches is associated with health risks for people who use it for recreational purposes. The present study focused on identifying wastewater discharges into seawater and describing the levels of contamination by fecal origin. It was possible to identify 6 wastewater dumping points along the coastal edge of the beach and 5 georeferenced monitoring points were considered for taking samples along El Murciélago beach in the city of Manta. The sampling campaign was carried out for a period of time of about one month, with 9 repetitions per sample, that is, 45 samples were obtained for their respective analysis. The methodology used for the fecal coliform count was through multiple tube fermentation (NMP). The results showed high levels of fecal coliforms in the first two weeks of sampling, values that were above the maximum permissible levels according to current environmental regulations in Ecuador. At monitoring points 3-4-5, maximum values of up to 1600 NMP/100ml were reached, while at points 1-2 relatively low values of fecal coliforms were obtained, with a maximum peak of 7.8 NMP/100ml. In the third and last week of monitoring, the microbiological analyzes showed that none of the samples exceeded the maximum levels required by environmental regulations, due to the beach recovery work carried out by the municipality, which consisted of eliminating the dumping of sewage at the coastline.